DIAGNOSA KECANDUAN GADGET PADA ANAK MENGGUNAKAN CERTAINTY FACTOR - Ike Verawati; Maria Yonessa Purwalasari (Jurnal Mantik Penusa)
Expert system is a system that uses human knowledge, where the knowledge is put into a computer and then used to solve problems that usually require expertise or human expertise. The expert system can function as a consultant who gives advice to users as well as advice for experts. One way to make it easier for parents of children aged 17-17 years to find out the level of addiction experienced by children is to build a web-based expert system to diagnose the level of gatget addiction in children aged 3-17 years web-based. The certainty factor method is a method for determining certainty. The purpose of this study is to build a web-based expert system to diagnose the level of gadget addiction in children aged 3-17 years, to simplify diagnosing the level of addiction experienced by children. The results of the gadget addiction diagnosis level produced by the expert system are the same as the results of the manual calculation using the certainty factor method. So it can be concluded that the web-based expert system that has been built can be used to diagnose the level of gadget addiction in children aged 3-17 years.